Metadado de gênero em registros de autoridade: proposta de diretrizes e enriquecimento semântico - Mendonça, Ana Carolina Novaes de (Universidade Federal de São Carlos, 2025)
The presence of gender metadata in authority records has become an emerging topic in the field of Information Science, especially in light of the growing demand for more inclusive, interoperable, and identity-aware systems of information and knowledge organization. In a context marked by the transformation of cataloging practices, driven by conceptual models, advances in Information and Communication Technologies, and the adoption of structured metadata standards, there arises a need to rethink how attributes such as gender are represented in bibliographic catalogs. This research aimed to analyze the presence and treatment of gender metadata in authority records maintained by national libraries, proposing guidelines and strategies based on semantic enrichment to enhance the quality of this representation in information systems. It is a qualitative investigation, with a descriptive and exploratory approach, based on bibliographic review, documentary analysis, and direct observation of public catalogs. Thirteen national libraries were analyzed, selected for their adoption of different metadata standards, in order to identify the fields used to represent gender, the values assigned, the controlled vocabularies employed, as well as the eventual linkage to external identifiers such as Wikidata and VIAF. The study also examined institutional guidelines, technical documents, and public policies related to the inclusion of gender metadata, when available. The results indicate that although metadata standards already provide specific fields for recording gender, their application remains limited, predominantly binary, and lacking standardization across the institutions analyzed. A lack of clear institutional policies for the use of these fields was observed, as well as a predominance of descriptive practices that overlook self-identification and the fluidity of gender identities. On the other hand, positive practices were identified, including the use of diversity-aware controlled vocabularies, linking to external URIs, and records aligned with open ontologies. It is concluded that the qualification of gender metadata in authority records, through the use of linked data technologies and semantic enrichment, can enhance the expressiveness, interoperability, and informational justice of bibliographic catalogs. The adoption of technical and ethical guidelines for such representation is essential to ensure the visibility of women authors, trans and non-binary individuals, and other identities frequently underrepresented in traditional systems. The research thus highlights the importance of normative and political advances to foster diversity and equity in informational environments.
Gender Metadata in Authority Records: proposal of guidelines and semantic enrichment
Keywords: Enriquecimento semântico; Gênero; Metadados; Registros de autoridade; Web semântica; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO